Changes in blood pressure in hypertension patients with kidney failure on drug valsartan administration in hospital - Diana Kholifah; Mayasari, Shinta; Khrisna Agung Cendekiawan (Sean Institute, 2024)
Hypertension an increase in blood pressure, including systolic and diastolic blood pressure into two types, namely essential hypertension, the most common being essential and secondary hypertension. The prevalence of hypertension in Indonesia using measurement methods in samples aged ≥18 years 34.1%, while the prevalence of hypertension cases in East Java province 36.3%. In pharmacological therapy the administration of drugs includes thiazide diuretics, adrenergic blockers, Angiotensin Converting Enzyme Inhibitors (ACE-inhibitors), angiotensin - II - blockers, in non-pharmacological therapy, namely changes in diet and lifestyle by consuming balanced foods according to needs, avoiding saturated fat, maintaining body weight, limiting salt consumption, the aim of knowing changes in blood pressure in hypertensive patients with kidney failure when administering the drug valsartan at Hospital Citra Husada. This research used a numerical comparative analytical research type with a retrospective design, the research was conducted in March, April 2023 at Citra Husada Hospital, the source of research data was from medical records. The sample obtained was 32 hypertensive patients with kidney failure who met the inclusion criteria, namely all genders aged 18 years and over, and outpatients at Hospital on a single drug (valsartan). Sampling used a total sampling technique, using Wilcoxon test data analysis to analyze changes in blood pressure. The average value of systolic blood pressure before administering the drug valsartan was 165.87 mmHg with a standard deviation of 27.06. The average systolic value after administering the drug valsartan was 151.15 mmHg with a standard deviation of 26.06, with a difference value of 14.72 mmHg. The average value of diastolic blood pressure before administering the drug valsartan was found to be 92.81 mmHg with a standard deviation of 20.16. The average diastolic value after administering the drug valsartan was found to be 81.09 mmHg with a standard deviation of 18.8, with a difference value of 11.72 mmHg. Conclusion: There are marked changes in blood pressure after administering the drug valsartan, valsartan can be recommended as an antihypertensive with kidney failure according to the inclusion criteria in the study.